Transporte de carga e modos vibracionais em sistemas desordenados de baixa dimensionalidade: potenciais harmônicos e não-lineares, interação elétron-fônon e efeitos de pulsos acústicos externos - Silva, Leônade Daviliano da (2018)
In this work we initial investigate the electronic dynamics in adisordered Fermi,Pasta, Ulam model under the presence of electron-phonon interaction and also a pumping of Gaussian acoustic pulses. We considered the electronic dynamics by using a quantum mechanics formalism and the nonlinear atomic vibrations by using standard classical physics. We study numerically the electronic propagation by numerical solution of the coupled quantum/classical equations. Our calculations suggest that the acoustic pumping asso ciated with the electron-lattice interaction promotes a sub-diffusive electronic dynamics. Concluding this first work, we studied the problem of a two-dimensional harmonic lattice in which the masses distribution is a superposition of a random and a periodic distribution. Classical equations for the mass displacement and velocities are solved using a second order Euler formalism. Energy flow was in vestigated on two distinct experiments: i) We injected na initial wave-packet with energy E0 and analyzed the dynamics of the resulting energy pulse; ii) we pumped one of the sides of the lattice with a external signal and then we observed the propagation of the pulse until the other side of chain. Our calculations suggest that the diluted disordered mass distribution promotes energy dynamics at high frequency limit.